2015
DOI: 10.1016/j.rinim.2013.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Effective anthelmintic therapy of residents living in endemic area of high prevalence for Hookworm and Schistosoma mansoni infections enhances the levels of allergy risk factor anti-Der p1 IgE

Abstract: In this work were investigated the relationship between Hookworm/Schistosoma mansoni infections and allergy related risk factors in two endemic areas with distinct prevalence of infections and co-infection. The intensity of infections, eosinophilia, allergy risk factors, infections status and anti-Der p1 IgE levels before and 2 years (population 1) and 3 years (population 2) after anthelmintic treatment, were evaluated. It was observed that the population with lower prevalence and intensity of infection (popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…This study demonstrated that, in the context of a population where the primary environmental stimulus for type 2 immune pathways (measured indirectly by total IgE) was helminth infection, the regulation of host immunity was also likely to be due to host genetic factors. A study of subjects coinfected with hookworm and S. mansoni has shown an increase in levels of anti‐Der p 1 IgE levels following chemotherapy, an effect that was independent of parasite burden …”
Section: Helminths and Allergy In Brazilmentioning
confidence: 99%
See 1 more Smart Citation
“…This study demonstrated that, in the context of a population where the primary environmental stimulus for type 2 immune pathways (measured indirectly by total IgE) was helminth infection, the regulation of host immunity was also likely to be due to host genetic factors. A study of subjects coinfected with hookworm and S. mansoni has shown an increase in levels of anti‐Der p 1 IgE levels following chemotherapy, an effect that was independent of parasite burden …”
Section: Helminths and Allergy In Brazilmentioning
confidence: 99%
“…A study of subjects coinfected with hookworm and S. mansoni has shown an increase in levels of anti-Der p 1 IgE levels following chemotherapy, an effect that was independent of parasite burden. 87 Human lymphatic filariasis, still present in parts of northern Brazil, causes chronic infections in humans that may persist for many years, and is associated with a profound modulation of host antiparasite immune responses. 88,89 A study of individuals with lymphatic filariasis with and without antigenemia showed higher frequencies of IFNγ-and IL-4-producing CD4 + T cells among patients without evidence of circulating microfilariae in the blood, consistent with a downregulation of immune responses among patients with patent infections 90 observed previously in non-Brazilian populations.…”
Section: >14%mentioning
confidence: 99%
“…However, more recent studies have suggested a protective role for symbiotic infectious agents in immune disorders. Interestingly, the presence of helminth infections was shown to reduce allergic atopy or atopic dermatitis, but conversely, treatment of helminths increased immune reactivity . Furthermore, studies showed that a reduction in helminth infection was associated with an increase in the incidence of inflammatory bowel disease .…”
Section: Hygiene Hypothesismentioning
confidence: 99%
“…Interestingly, the presence of helminth infections was shown to reduce allergic atopy or atopic dermatitis, but conversely, treatment of helminths increased immune reactivity. [18][19][20][21] Furthermore, studies showed that a reduction in helminth infection was associated with an increase in the incidence of inflammatory bowel disease. 22 These studies raise the important question: how do these factors affect the immune system?…”
Section: Hygiene Hypothesismentioning
confidence: 99%
“…Asthmatics individuals infected with Schistosoma mansoni have less severe asthma symptoms as compared to uninfected patients. Moreover, the anthelmintic treatment against S. mansoni led to a worsening of asthma symptoms and to an increase in allergenspecific serum IgE (Almeida et al, 2012;Campolina et al, 2013;Medeiros et al, 2003;Van den Biggelaar et al, 2004). Furthermore, infection with S. mansoni has been associated with a reduced Th2 response in vitro and in murine model with an increase in regulatory mechanisms that may be associated with the control of inflammation and improvement in asthma symptoms (Araujo et al, 2004;Oliveira et al, 2009;Smits et al, 2007).…”
Section: Introductionmentioning
confidence: 99%